A bakonyi "villámhadjárat" 1598. július-augusztus - Tóth Sándor László (SZTE BTK Történeti Intézet Szeged, 2021)
During the so-called Long War or Fifteen Years War (1593–1606) between the Ottoman and the Habsburg Empires this two weeks campaign (30 July – 12 August 1598) was one of the most successful military operation of the imperial armies. After the first five years of changing luck – loss of Győr and Eger and the defeat at Mezőkeresztes and the recapture of Esztergom – in March 1598 Győr was regained in one day. In the summer of 1598 the allied Christian army (about 20.000 soldiers), led by General Adolf von Schwarzenberg and assisted by Miklós Pálffy and others, reoccupied 8 forts from the Ottomans: Tata, Gesztes, Csókakő, Palota, Veszprém, Vázsony, Tihany and Csesznek. Only Tata and Palota offered resistance, the guards of the other fortresses just fled. The study analyzes with the help of archival and secondary sources the structure of the imperial army, the events and importance of this lightning war in the east Transdanubian territory of Hungary belonging to the Vilayet of Buda at that time.
Keywords: Bölcsészettudományok; Történettudomány és régészet